ملامح الرؤية الكونية الإسلامية عند الشيخ محمد أسد - زهية بوحنيك (university of eloued جامعة الوادي, 2025)
This study aims to identify the features of the cosmological vision of Sheikh Muhammad Asad. The cosmological vision of Muhammad Asad (Leopold Weiss) is characterized by its pure monotheism and comprehensiveness that encompasses all aspects of life, balancing reason and revelation, and promoting ethics and human values. Asad emphasizes liberating humans from servitude to creatures and directing them towards the worship of God alone, granting them dignity and responsibility as God's vicegerents on Earth. He underscores the importance of social solidarity and positive interaction with the universe, encouraging scientific research and contemplation of God's signs. He also links the temporal and the eternal, viewing this life as a preliminary test stage for eternal life, urging humans to perform good deeds and prepare for their final destiny, thereby leading a life oriented towards God's pleasure and the cultivation of the earth with justice and benevolence.جاءت هذه الدراسة بهدف تحديد ملامح الرؤية الكونية عند الشيخ محمد أسد. تتميز الرؤية الكونية عند محمد أسد (ليوبولد فايس) بتوحيدية خالصة وشمولية تتناول جميع جوانب الحياة، حيث توازن بين العقل والوحي، وتعزز الأخلاق والقيم الإنسانية. يركز أسد على تحرير الإنسان من العبودية للمخلوقات وتوجيهه نحو عبادة الله وحده، مما يمنحه كرامة ومسؤولية كخليفة لله في الأرض. يشدد على أهمية التكافل الاجتماعي والتفاعل الإيجابي مع الكون، مشجعاً على البحث العلمي والتأمل في آيات الله. كما يربط بين الدنيا والآخرة، حيث يرى الحياة الدنيا كمرحلة اختبار تمهيدية للحياة الأبدية، مما يحث الإنسان على العمل الصالح والاستعداد لمصيره النهائي، ليعيش حياة موجهة نحو رضا الله وإعمار الأرض بالعدل والإحسان.
Keywords: الرؤية الكونية، الرؤية الإسلامية، محمد أسد.; cosmological vision; Islamic vision; Muhammad Asad.